2012
DOI: 10.1111/j.1749-6632.2012.06762.x
|View full text |Cite
|
Sign up to set email alerts
|

Janus‐faced role of SIRT1 in tumorigenesis

Abstract: Silent mating type information regulation 1 (Sirtuin 1; SIRT1) has been reported to regulate various physiological events, such as aging and metabolism, via deacetylation of histone and nonhistone proteins. Notably, cumulative evidence supports the notion that SIRT1 has a Janus-faced role in tumorigenesis. SIRT1 contributes to anti-inflammation, genomic stability, and cancer cell death, and hence it has tumor-suppressor properties. On the other hand, SIRT1 can stimulate oncogenic signaling pathways and can cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 98 publications
(312 reference statements)
1
107
0
Order By: Relevance
“…Its deacetylation activity enables it to interact with a variety of important transcription factors and transcriptional co-regulatory factors, to regulate gene transcription, chromosome stability and activity of target proteins, which are involved in tumor metabolism and development (5,6). The current results demonstrated that SIRT1 plays a dual role as a tumor promoter as well as a tumor suppressor (7). Its involvement in tumorigenesis may be due to its diverse distribution in different tissues and different upstream and downstream regulatory factors that regulate its function (8).…”
Section: Introductionmentioning
confidence: 74%
“…Its deacetylation activity enables it to interact with a variety of important transcription factors and transcriptional co-regulatory factors, to regulate gene transcription, chromosome stability and activity of target proteins, which are involved in tumor metabolism and development (5,6). The current results demonstrated that SIRT1 plays a dual role as a tumor promoter as well as a tumor suppressor (7). Its involvement in tumorigenesis may be due to its diverse distribution in different tissues and different upstream and downstream regulatory factors that regulate its function (8).…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, altered intracellular localization likely changes the interactions with target proteins. Other studies have shown that intracellular Sirt1 localization changes in response to physiologic and pathologic stimuli resulting in altered cell differentiation and different roles during multistage carcinogenesis (22,36,37). The functional impact of these changes in Sirt1 in pancreas was explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these Janus-faced roles in cancer promotion, SIRT1 might determine tumor responses to anticancer drugs. Although SIRT1 has not been intensively explored in terms of cancer chemotherapy, previous studies have supported the notion that SIRT1 plays some positive roles in tumor acquisition of chemoresistance (19). Whether SIRT1 participates in the hypoxia-induced chemoresistance is unclear.…”
Section: Introductionmentioning
confidence: 99%